Residual Force Method for damage identification in a laminated composite plate with different boundary conditions - Amar Behtani; Samir Tiachacht; Tawfiq Khatir; Samir Khatir; Magd Abdel Wahab; Brahim Benaissa (Fracture and Structural Integrity)
The strongest point about damage identification based on the dynamic measurements, is the ability perform structural health evaluation globally. Researchers in the last few years payed more attention to damage indicators based on modal analysis using either frequencies, mode shapes, or Frequency Response Functions (FRFs). This paper presents a new application of damage identification in a cross-ply (0°/90°/0°) laminated composite plate based on Force Residual Method (FRM) damage indicator. Considering single and multiple damages with different damage levels. As well as investigating the SSSS and CCCC boundary conditions effect on the estimation accuracy. Moreover, a white Gaussian noise is introduced to test the challenge the technique. The results show that the suggested FRM indicator provides accurate results under different boundary conditions. Favouring the SSSS boundary condition than the CCCC for 3% noise.